ANALISIS CULTURALLY RESPONSIVE TEACHING FOR MEANINGFULL LEARNING DI SD NEGERI PEPELEGI II - Sari, Della Puspita; Rachmadyanti, Putri; Alfiyah, Umi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in Indonesia today has become a crucial aspect for the younger generation in facing future life challenges. The government has placed significant emphasis on the quality of education to cultivate educated and knowledgeable generations. One of the implementations of this focus is the "Merdeka Curriculum," which emphasizes an understanding of freedom in learning and humanizing humans according to their natural state and era. As part of the Merdeka Curriculum, the Culturally Responsive Teaching (CRT) approach has been introduced to facilitate learning that considers the sociocultural context of the students. This study aims to describe the implementation of the CRT approach for meaningful learning at SD Negeri Pepelegi II Sidoarjo. The research method used is qualitative, with data collection through observation during learning activities, observation of student assessment results, and interviews with teachers and students. The findings indicate that the implementation of the CRT approach at SD Negeri Pepelegi II Sidoarjo provides meaningful learning experiences for the students. Teachers who adopt this approach recognize and appreciate students' cultural identities, build inclusive relationships, and center the learning process on the students. Additionally, they utilize various cultural artifacts in learning, such as local music and songs, to enhance student engagement and understanding of the learning material. This research demonstrates that the CRT approach not only improves academic performance but also helps students experience relevant, profound, and inclusive learning.